Is it time to tailor treatments in androgen receptor positive salivary gland cancers?. (January 2023) - Bossi, Paolo; Lorini, Luigi; Cosentini, Deborah; Grisanti, Salvatore; Battocchio, Simonetta; Berruti, Alfredo
Highlights: Enzalutamide has a promising activity in preselected androgen receptor positive salivary gland carcinomas. In castration sensitive patients, high testosterone levels may hindered enzalutamide activity. Molecular and different phenotypic selection of androgen receptor positive salivary gland carcinomas may lead to tailor treatment for such patients.